Novel grading system of sigmoid sinus dehiscence for radiologic evaluation of pulsatile tinnitus. (May 2021) - Willis, Shelby; Duong, Courtney; Yang, Isaac; Gopen, Quinton
Highlights: Novel grading system for sigmoid sinus dehiscence based on size and location. Sigmoid sinus dehiscence up to 7.5 mm may be a normal variant in asymptomatic patients. Sigmoid sinus dehiscence found on CT scan in 34% of asymptomatic cohort. Abstract: Background: Sigmoid sinus dehiscence (SSD) is an important etiology of pulsatile tinnitus (PT) though there is currently no consensus on the prevalence of SSD in non-PT populations. This study establishes a grading system of SSD and analyzes a non-PT cohort for prevalence of SSD. Methods: In this retrospective study temporal bone CT scans of 91 patients without PT were analyzed for SSD. The dehiscence was divided into three grades: Grade 1 indicating a micro dehiscence of <3.5 mm with an opening to the mastoid air cells, Grade 2 indicating a major dehiscence of >3.5 mm with an opening to the mastoid air cells, and Grade 3 indicating a sigmoid sinus wall dehiscence opening directly to the underlying tissue. Results: In patients without PT, SSD occurred in 34% of the cohort. Of these, 75% were Grade 1 and 25% were Grade 2. The range of dehiscence measurements for Grade 1 dehiscences was 0.9–3.4 mm. The range of dehiscence measurements for Grade 2 was 4–7.5 mm. There were no cases of Grade 3 dehiscence among this cohort. Conclusions: SSD occurred in over a third of our non-symptomatic cohort. While all grades of SSD may currently be treated surgically, a large portion of non-PT patients may have these sigmoid sinus anomalies asymptomatically. This grading system allows for the standardization of SSD definition and severity in future studies. Grade 3 dehiscences were completely absent in this cohort of non-PT patients.